Association of apolipoprotein E polymorphism in late-onset Alzheimer's disease and vascular dementia in Brazilians - Souza, D. R. S.; Godoy, M. R. de; Hotta, J.; Tajara, E. H. [UNESP]; Brandão, A. C.; Pinheiro Júnior, S.; Tognola, W. A.; Santos, J. E. dos (Associação Brasileira de Divulgação Científica (ABRADIC), 2003)
The genetic basis for dementias is complex. A common polymorphism in the apolipoprotein E (APOE) gene is considered to be the major risk factor in families with sporadic and late-onset Alzheimer's disease as well as in the general population. The distribution of alleles and genotypes of the APOE gene in late-onset Alzheimer's disease (N = 68), other late-life dementias (N = 39), and in cognitively normal controls (N = 58) was determined, as also was the risk for Alzheimer's disease associated with the epsilon4 allele. Peripheral blood samples were obtained from a total of 165 individuals living in Brazil aged 65-82 years. Genomic DNA was amplified by the polymerase chain reaction and the products were digested with HhaI restriction enzyme. APOE epsilon2 frequency was considerably lower in the Alzheimer's disease group (1%), and the epsilon3 allele and epsilon3/epsilon3 genotype frequencies were higher in the controls (84 and 72%, respectively) as were the epsilon4 allele and epsilon3/epsilon4 genotype frequencies in Alzheimer's disease (25 and 41%, respectively). The higher frequency of the epsilon4 allele in Alzheimer's disease confirmed its role as a risk factor, while epsilon2 provided a weak protection against development of the disease. However, in view of the unexpectedly low frequency of the epsilon4 allele, additional analyses in a more varied Brazilian sample are needed to clarify the real contribution of apolipoprotein E to the development of Alzheimer's disease in this population.
Keywords: Alzheimer's disease; Vascular dementia; Dementia; Apolipoprotein E; Aging; Genetic polymorphisms